Information Literacy Overload and the Impact of Misinformation, Disinformation and eInformation on End-Users of Hard Copy and On-line Publications. - Amoriggi, Helen (International Journal of the Book, 2007)
Successive research studies indicate that the last two decades have seen the greatest proliferation of print and ePrint in mankind's history and there is more to come. Unfortunately, reading productivity and the skills to maximize the intake of these abundant resources have simply not kept pace with their prolific digitized dissemination. The word per minute reading rate (WPM) has remained mired at the rate of speech (under 300 WPM) since Gutenberg reinvented the press. Despite warnings heralded by information overload researchers, the pervasive and ubiquitous eInformation-based text treatment has still not been integrated or even addressed by academia where the 'publish or perish' philosophy has remained the creed. The post-graduate eLearner of the 21st Century can no longer rely on the antiquated systems of teaching reading and note-taking that are prevalent in education today. The private sector has moved forward with successful training programs dealing with the eInformation Literacy explosion, whereas academia has not. This paper is focused on this issue.